Adopting E-Learning Platforms in Tourism Schools in Bali: Challenges and Opportunities - Luh Sri Damayanti; Ni Luh Kadek Laksmi Wulandani; Evan Afri (ITScience (Information Technology and Science), 2024)
This study aimed to analyze the implementation of online English learning in tourism schools in Bali, focusing on the strengths, weaknesses, opportunities, and threats associated with its execution. Employing a qualitative research approach, the study involved four English lecturers from four different tourism schools in Bali. Data were collected through observations, interviews, and literature reviews. The analysis revealed that online English learning was conducted using the English for Specific Purposes (ESP) framework, tailored to the tourism and hospitality sectors. The implementation involved various platforms, including Zoom Meeting, WhatsApp, and other digital tools. Strengths identified included the flexibility of time and space, allowing both lecturers and students to access learning materials from any location at any time. The availability of diverse online platforms provided lecturers with the ability to customize their teaching methods effectively. However, weaknesses covered technical issues, including inadequate devices and unstable internet connections, posed significant challenges. The study also highlighted the opportunities presented by the increasing digital literacy of students and the proliferation of online learning platforms, which facilitated a more interactive and engaging learning experience. Nonetheless, threats included low public awareness, particularly among parents, and varying levels of digital proficiency among lecturers, which impacted the overall effectiveness of online instruction. The findings underscore the need for enhanced support structures and training to optimize online English learning in tourism education.